2005
DOI: 10.1093/nar/gki555
|View full text |Cite
|
Sign up to set email alerts
|

ZAC, LIT1 (KCNQ1OT1) and p57KIP2 (CDKN1C) are in an imprinted gene network that may play a role in Beckwith-Wiedemann syndrome

Abstract: Loss of genomic imprinting is involved in a number of developmental abnormalities and cancers. ZAC is an imprinted gene expressed from the paternal allele of chromosome 6q24 within a region known to harbor a tumor suppressor gene for several types of neoplasia. p57KIP2 (CDKN1C) is a maternally expressed gene located on chromosome 11p15.5 which encodes a cyclin-dependent kinase inhibitor that may also act as a tumor suppressor gene. Mutations in ZAC and p57KIP2 have been implicated in transient neonatal diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 48 publications
2
86
1
4
Order By: Relevance
“…Although the predicted pattern of paternallyexpressed imprinted genes tending to foster overall growth, and maternallyexpressed imprinted genes constraining it, has been abundantly supported in studies of placentation and body size (e. g., Plagge et al, 2004;Weinstein et al, 2004;Kelsey 2007), the simple, direct tug-of-war system exemplified by Igf2 and its receptor has proven to be atypical of imprinted-gene effects generally. The first clear evidence for a much more extensive system of imprinted-gene interactionimprinted-gene networks -emerged from work by Arima et al (2005), who demonstrated that the imprinted genes ZAC1, LIT1, and CDKN1C jointly mediate growth of human cells. Varrault et al (2006) used information from experimental mouse knockouts, and microarray databases, to document more directly the existence of a co-regulatory imprinted-gene network; thus, gains and losses of Zac1 altered the expression levels of the imprinted genes Igf2, H19, Cdkn1c and Dlk1, and a broad pattern of imprinted-gene coexpression, involving these five genes as well as Grb10, Gtl2, Peg1 (Mest), Sgce, Dcn, Gatm, Gnas, Ndn, and Peg3, emerged from analyses of gene-coexpression in pooled datasets from mouse muscle and other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although the predicted pattern of paternallyexpressed imprinted genes tending to foster overall growth, and maternallyexpressed imprinted genes constraining it, has been abundantly supported in studies of placentation and body size (e. g., Plagge et al, 2004;Weinstein et al, 2004;Kelsey 2007), the simple, direct tug-of-war system exemplified by Igf2 and its receptor has proven to be atypical of imprinted-gene effects generally. The first clear evidence for a much more extensive system of imprinted-gene interactionimprinted-gene networks -emerged from work by Arima et al (2005), who demonstrated that the imprinted genes ZAC1, LIT1, and CDKN1C jointly mediate growth of human cells. Varrault et al (2006) used information from experimental mouse knockouts, and microarray databases, to document more directly the existence of a co-regulatory imprinted-gene network; thus, gains and losses of Zac1 altered the expression levels of the imprinted genes Igf2, H19, Cdkn1c and Dlk1, and a broad pattern of imprinted-gene coexpression, involving these five genes as well as Grb10, Gtl2, Peg1 (Mest), Sgce, Dcn, Gatm, Gnas, Ndn, and Peg3, emerged from analyses of gene-coexpression in pooled datasets from mouse muscle and other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This would put ZAC, KCNQ1OT1 and CDKN1C in a common regulatory network that influences intrauterine growth. (61) To understand how diseases such as SRS, BWS and TNDM can arise from epigenetic alterations, it should be important to further explore the mechanisms that maintain the allele-specific DNA methylation at ICRs. Apart from the clear involvement of DNA methyltransfereases, this is largely an outstanding question.…”
Section: Introductionmentioning
confidence: 99%
“…Zac1's antiproliferative actions in mesenchymal and neural progenitor/stem cells indicates its importance for cell fate and lineage decisions (36,37). Previous studies demonstrate that either monomeric or dimeric Zac1 binding to GC-rich palindromic elements or to GC-rich direct-and reverse-repeat elements (4,16,38) underlies the activation of the H19, Lit1, peroxisome proliferatoractivated receptor gamma, and CK14 target genes (1,3,16,39).Quite unexpectedly, Zac1 was isolated in a yeast screen for mammalian coregulator proteins that bind to the carboxylterminal activation domain of the nuclear receptor coactivator SRC-2 (18). Consistent with its putative role as a coactivator, Zac1 additionally associated with the ligand-binding domains of the androgen, estrogen, glucocorticoid, and thyroid hormone receptors and potently enhanced the transcriptional activities of these nuclear receptors.…”
mentioning
confidence: 99%
“…Zac1's antiproliferative actions in mesenchymal and neural progenitor/stem cells indicates its importance for cell fate and lineage decisions (36,37). Previous studies demonstrate that either monomeric or dimeric Zac1 binding to GC-rich palindromic elements or to GC-rich direct-and reverse-repeat elements (4,16,38) underlies the activation of the H19, Lit1, peroxisome proliferatoractivated receptor gamma, and CK14 target genes (1,3,16,39).…”
mentioning
confidence: 99%